Magnetic nanotherapeutics for dysregulated synaptic plasticity during neuroAIDS and drug abuse. Issue 1 (December 2016) - Sagar, Vidya; Atluri, Venkata; Pilakka-Kanthikeel, Sudheesh; Nair, Madhavan
Abstract The human immunodeficiency virus (HIV) is a neurotropic virus. It induces neurotoxicity and subsequent brain pathologies in different brain cells. Addiction to recreational drugs remarkably affects the initiation of HIV infections and expedites the progression of acquired immunodeficiency syndrome (AIDS) associated neuropathogenesis. Symptoms of HIV-associated neurocognitive disorders (HAND) are noticed in many AIDS patients. At least 50 % of HIV diagnosed cases show one or other kind of neuropathological signs or symptoms during different stages of disease progression. In the same line, mild to severe neurological alterations are seen in at least 80 % autopsies of AIDS patients. Neurological illnesses weaken the connections between neurons causing significant altercations in synaptic plasticity. Synaptic plasticity alterations during HIV infection and recreational drug abuse are mediated by complex cellular phenomena involving changes in gene expression and subsequent loss of dendritic and spine morphology and physiology. New treatment strategies with ability to deliver drugs across blood-brain barrier (BBB) are being intensively investigated. In this context, magnetic nanoparticles (MNPs) based nanoformulations have shown significant potential for target specificity, drug delivery, drug release, and bioavailability of desired amount of drugs in non-invasive brain targeting. MNPs-based potential therapies to promote neuronal plasticity during HIV infection and recreational drug abuse are being developed.